Design of a Teaching Module for Drawing Electrical Installations in the Technical Drawing Course at SMKN 2 Meulaboh - Siddiq, Ilham; Baihaqi (PTE FTK UIN Ar-Raniry, 2026)
The Technical Drawing course is part of the curriculum at SMK Negeri 2 Meulaboh, West Aceh, particularly for students specializing in Electrical Power Installation Engineering. Electrical installation diagrams play a crucial role in designing installation processes, as projects can only be implemented through drawings equipped with specific electrical symbols. Given that the Technical Drawing course at SMK Negeri 2 Meulaboh predominantly uses lecture-based methods, the researcher aims to develop a module to facilitate the learning process. The chosen methodology is Research and Development (R&D), which involves a systematic process for developing or optimizing a product. The research instruments include a validation sheet to test the feasibility of the designed module and a questionnaire to gather responses regarding its use. The validation results from media experts, subject matter experts, and language experts achieved percentages of 86%, 87%, and 90%, respectively, indicating that the designed module for drawing electrical installations is highly feasible for implementation in the Technical Drawing course. Meanwhile, the questionnaire results show an average percentage of 87% across all indicators, proving that the module is